Functional anatomy and kinematics of the oral jaw system during terrestrial feeding in Periophthalmus barbarus. (5th May 2014) - Michel, Krijn B.; Adriaens, Dominique; Aerts, Peter; Dierick, Manuel; Wassenbergh, Sam Van
ABSTRACT The Atlantic mudskipper, Periophthalmus barbarus, is an amphibious fish that successfully overcomes the numerous physical challenges of capturing prey in a terrestrial environment. However, it is unclear what changes in the morphology and function of the feeding apparatus contribute to the mudskipper's successful transition from aquatic to terrestrial capture of prey. In particular, how does the mudskipper achieve effective prehension of land‐based prey using its percomorph feeding apparatus? To address that question, we performed a morphological analysis of the feeding apparatus of P. barbarus based on microcomputed tomography scanning, histological sectioning, and dissections as well as a kinematic analysis based on high‐speed video and X‐ray video to quantify the movements of the oral jaw apparatus elements. Our results show that the neurocranium remains in a fixed position relative to the pectoral girdle as the fish pivots over its pectoral fins toward the prey. The premaxilla rotates dorsally and protrudes downward over the prey. The dentary is rotated ventrally over an angle of 120°, which is facilitated by an intramandibular joint. These motions of the neurocranium, premaxilla, and dentary reorient the mouth aperture so it is parallel to the substrate, thereby allowing the jaws to be placed over the prey. The prey is grabbed between the oral teeth or scooped into the mouth primarily via rapid closing motion of the lower jaw. This analysis of P. barbarus clarifies the morphological and kinematic characteristics required by fish to become successful terrestrial feeders at the environmental transition between water and land. J. Morphol. 275:1145–1160, 2014. © 2014 Wiley Periodicals, Inc.